Clarithromycin does not affect phosphorylation of zidovudine in vitro. - Rana, K Z (1996)
Zidovudine (ZDV) and clarithromycin (CLR) are often used simultaneously in the management of patients with AIDS. While pharmacokinetic studies show decreased absorption of ZDV when it is administered with CLR, it is unknown if CLR affects the intracellular metabolism of ZDV. We investigated the effects of CLR on the intracellular metabolism of ZDV in vitro. CEM-T4 cells were coincubated with a microM ZDV ([3 H] ZDV, 3 microCi/ml) either alone or with 1 or 10 microM CLR. Cells were also grown in the presence of CLR for 48 h prior to exposure to ZDV. Samples were analyzed for mono-, di-, and triphosphate metabolites of [3 H] ZDV by high-performance liquid chromatography separation and radiochemical detection. There were no significant differences in levels of intracellular metabolites of ZDV following exposure to ZDV, either alone or with 1 or 10 microM CLR and under both coincubated and preincubated conditions. These results show that treatment with CLR does not alter the formation of phosphorylated metabolites of ZDV in this cell line.